Introducing Knowledge Translation to Plastic Surgery: Turning Evidence into Practice. Issue 5 (November 2018) - Moltaji, Syena; Alkhatib, Ahmad H.; Liu, Henry; Murphy, Jessica; Gallo, Lucas; Karpinski, Marta; Mowakket, Sadek; Thoma, Achilleas
Abstract : Summary: Best evidence has no bearing on quality of life if it is not implemented in clinical practice. The authors introduce knowledge translation as a theoretical framework for closing the gap between evidence and practice in plastic surgery. The current state of published evidence in plastic surgery is reviewed and evaluated, with the recommendation to use the EQUATOR Network's guidelines for reporting clinical research findings. Tools and strategies are offered for the reader to understand and integrate evidence at the bedside. Systemic solutions are also proposed for the dissemination of best evidence to facilitate its translation into practice.